2015
DOI: 10.1002/clen.201400085
|View full text |Cite
|
Sign up to set email alerts
|

Alleviating Effect of Calcium on Nickel Toxicity in Rice

Abstract: Urbanization and industrialization have resulted in contamination of soils with heavy metals and other pollutants. Nickel (Ni) is one of the toxic metals, which adversely affect plant growth by altering different physiological and metabolic processes. Mineral nutrients can reduce toxic effects of Ni on physiological and metabolic functions of plants, thus improving plant growth. The role of calcium (Ca) to alleviate Ni toxicity in rice was investigated. Rice plants were grown with Ni (20 and 40 mg kg−1) and Ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 55 publications
1
31
0
Order By: Relevance
“…Therefore, it is possible that exchangeable Ca can compete with metals in plants from site 1. The competition between Ca and metals was observed by other authors (Li et al 2009;Wang et al 2010;Yusuf et al 2011;Lago-Vila et al 2015;Aziz et al 2015). For example, Li et al (2009) andLago-Vila et al (2015) suggested that exchangeable Ca can decrease Ni and Co accumulation by plants because of competition for binding sites in root cells.…”
Section: Accumulation Of Metals By Plantsmentioning
confidence: 60%
See 1 more Smart Citation
“…Therefore, it is possible that exchangeable Ca can compete with metals in plants from site 1. The competition between Ca and metals was observed by other authors (Li et al 2009;Wang et al 2010;Yusuf et al 2011;Lago-Vila et al 2015;Aziz et al 2015). For example, Li et al (2009) andLago-Vila et al (2015) suggested that exchangeable Ca can decrease Ni and Co accumulation by plants because of competition for binding sites in root cells.…”
Section: Accumulation Of Metals By Plantsmentioning
confidence: 60%
“…Consequently, activity of metals was lower and toxicity was alleviated. Aziz et al (2015) used rice for studying interactions between Ca and Ni. The presence of Ca in tested soils caused decrease in Ni content in plants due to improvement metabolic functions of cell membrane and maintaining its integrity.…”
Section: Accumulation Of Metals By Plantsmentioning
confidence: 99%
“…Studies on the contamination of Ni in soils and plants have so far been restricted to highly industrialized temperate regions (AlHamdan and Reddy, 2006). Ni adversely affects plant growth by altering different physiological and metabolic processes (Aziz et al, 2015). So the accumulation of these metals in soil may cause the environmental pollution to a great extent.…”
Section: Introductionmentioning
confidence: 99%
“…Although the role of Ca in increasing metal (including Ni) tolerance has previously been documented (Chaney et al 2008;Siddiqui et al 2011;Aziz et al 2015), the exact mechanisms involved in minimizing toxicity are not always elaborated. Further, there is limited work to date examining the role of CAX1 in serpentine tolerance, including in the tolerance of Ni.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of Ca in alleviating metal toxicity is also known (Aziz et al 2015). Calcium is an essential nutrient for plant growth, development, and metabo- lism, regulating the function of proteins and membrane transport systems as well as gene expression (Bush 1995;White and Broadley 2003;Hepler 2005).…”
Section: Introductionmentioning
confidence: 99%